Factors Influencing Parental Satisfaction in Education: A Case Study of State High School 1 Berastagi - Tuhu Edi Arihta Sembiring; Giovani Syahputra (Journal Basic Science and Technology, 2024)
This research delves into the intricate dynamics of parental satisfaction at State High School 1 Berastagi, aiming to identify key factors influencing parental attitudes and perceptions towards education. Drawing upon a mixed-methods approach, including quantitative surveys and qualitative interviews, the study explores dimensions such as academic quality, teacher-student interactions, school climate, extracurricular opportunities, and parental involvement. Findings reveal varying levels of parental satisfaction across different dimensions, with academic quality emerging as a primary driver of satisfaction. Positive teacher-student interactions, a supportive school climate, and meaningful parental involvement also significantly contribute to parental satisfaction. Moreover, contextual factors such as cultural norms and socio-economic disparities influence parental perceptions and experiences. Implications for educational practice and policy are discussed, emphasizing the importance of enhancing academic quality, promoting positive relationships, fostering a positive school climate, providing diverse extracurricular opportunities, and promoting meaningful parental involvement. The study concludes with reflections on its limitations and suggests directions for future research to further enrich our understanding of parental satisfaction and inform evidence-based interventions and policies aimed at enhancing the quality of education for all stakeholders.